ANALISIS SISTEM PEMUNGUTAN PAJAK KENDARAAN ALAT BERAT TERHADAP EFEKTIFITAS PENDAPATAN ASLI DAERAH PROVINSI KALIMANTAN BARAT - B51112115, HENDRI JONATHAN (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The aim of this research is to find out the mechanism or system and tax collection procedures on heavy equipment carried out by the Tax and Revenues Office of West Kalimantan Province and to find out the level of effectiveness of tax collection on heavy equipment to the locally generated revenues. This research used a case study method taking Tax and Revenues Office of West Kalimantan Province (DISPENDA) as the object. The data were collected using interviews, questionnaires, and literature study. The analytical tool used in this research was the flowchart analysis to find out the flow of documents and operational procedures in collecting tax on heavy equipment, the organizational structure analysis to investigate the relationship between functions within the organization, and the division of tasks, the Internal Control Questionnaire (ICQ) to find out the internal control, the effectiveness analysis to measure the effectiveness of tax on heavy equipment to locally generated revenues. The research findings showed that the system and procedures for tax collection on heavy equipment carried out the Tax and Revenues Office of West Kalimantan Province were in accordance with the Regional Regulation No. 8/2010 and the Internal Control implemented was quite good, and the level of effectiveness was very good despite a decrease and some weaknesses which need to be taken into consideration and improved further by the Tax and Revenues Office of West Kalimantan (DISPENDA). Keywords: Flowchart, Internal Control Questionnaire (ICQ), Internal Control System.